ANALISIS KOMPARATIF TINGKAT KEPUASAN MAHASISWA TERHADAP KUALITAS PELAYANAN BSI PERBANKAN LANGSUNG DAN MOBILE BANKING PADA MAHASISWA IAIN LHOKSEUMAWE ANGKATAN 2017 - Nora Maulana; Muhammad Syafril Nasution (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
Technological progress has its own role for financial institutions, including BSI inorder to provide excellent service to customers. Productive customer assessmentsand responses in this case students are very important. This study aims todetermine the difference in the level of student satisfaction with the quality of BSIdirect banking services with BSI mobile banking. This research is a field researchwith a mixed method approach and is comparative in nature. The population in thestudy were all students of IAIN Lhokseumawe class of 2017 who were BSI bankcustomers as many as 280 respondents were selected based on purposive sampling.Data collection methods used were questionnaires, interviews, and documentation.The results of the study through the help of SPSS 21 for windows, the U testshowed differences in responses in the eyes of students with a significance value(2-tailed) of 0.000 which means 0.000 < 0.05 then H0 is rejected and H1 isaccepted..